Patent remedies and complex products : toward a global consensus - Contreras, Jorge L.; Biddle, Brad, 1968-; Love, Brian J. (Law teacher); Sibrasse, Norman, 1961- (Cambridge : Cambridge University Press, 2019)
Through a collaboration among twenty legal scholars from eleven countries in North America, Europe and Asia, Patent Remedies and Complex Products presents an international consensus on the use of patent remedies for complex products such as smartphones, computer networks and the Internet of Things. It covers the application of both monetary remedies like reasonable royalties, lost profits, and enhanced damages, as well as injunctive relief. Readers will also learn about the effect of competition laws and agreements to license standards-essential patents on terms that are'fair, reasonable and non-discriminatory' (FRAND) on patent remedies. Where national values and policy make consensus difficult, contributors discuss the nature and direction of further research required to resolve disagreements. This title is also available as Open Access on Cambridge Core.
Foreword / Kathleen M. O'Malley -- Reasonable royalties / Thomas F. Cotter, John M. Golden, Oskar Liivak, Brian J. Love, Norman V. Siebrasse, Masabumi Suzuki and David O. Taylor -- Lost profits and disgorgement / Christopher B. Seaman, Thomas F. Cotter, Brian J. Love, Norman Siebrasse and Masabumi Suzuki -- Enhanced damages, litigation cost recovery, and interest / Colleen V. Chien, Jorge L. Contreras, Thomas F. Cotter, Brian J. Love, Christopher B. Seaman and Norman V. Siebrasse -- Injunctive relief / Norman V. Siebrasse, Rafal Sikorski, Jorge L. Contreras, Thomas F. Cotter, John M. Golden, Sang Jo Jong, Brian J. Love and David O. Taylor -- The effect of FRAND commitments on patent remedies / Jorge L. Contreras, Thomas F. Cotter, Sang Jo Jong, Brian J. Love, Nicolas Petit, Peter Picht, Norman V. Siebrasse, Rafal Sikorski, Masabumi Suzuki and Jacques de Werra -- The effect of competition law on patent remedies / Alison Jones and Renato Nazzini -- Holdup, holdout, and royalty stacking : a review of literature / Norman V. Siebrasse.
Title from publisher's bibliographic system (viewed on 05 Jul 2019).
Keywords: Patent laws and legislation; Remedies (Law)